[Polc, Jaroslav V., ed. Svatý Vojtěch: sborník k mileniu] - Krafl, Pavel (Religio, 1998)
Reviewed works: Polc, Jaroslav V., ed. Svatý Vojtěch: sborník k mileniu. 1. vyd. Praha: Zvon, 1997. 275 s. ISBN 80-7113-193-8.